Recurrent iridocyclitis due to cotton fiber in anterior chamber - Joshi, Rajesh S (Nepalese Journal of Ophthalmology, 2016)
Background: Cotton is commonly used during ophthalmic surgical procedure. Cotton fibers may get attracted to the instruments due to electrostatic forces and become adhered to the surface. With the introduction of these instruments during the surgical procedure cotton fiber may get entry into the eye. In the literature they have been infrequently reported due to insignificant effect on the ocular structures. We present a case of recurrent iridocyclitis due to cotton fiber in the anterior chamber. Patient was relived of his symptoms after removal. Case: A 78-year-old male presented with pain, redness and blurring of right eye vision since last six months. The patient had undergone phacoemulsification with implantation of hydrophilic intraocular lens (IOL) six years earlier. Postoperative follow up was uneventful from his records till last 6 months. Slit-lamp examination revealed a cotton fiber in the anterior chamber touching the endothelium. Keratic precipitates were seen on the endothelium. Removal of the cotton fiber resulted in subsidence of inflammation. Conclusion: We recommend use of plastic eye and trolley drapes, lint free instrument wipes and use of needle cap to support the globe during creation of side port while performing phacoemulsification instead of cotton buds to avoid entry of cotton fiber into the anterior chamber. Nepal J Ophthalmol 2016; 8(15): 87-90